The stories are burning inside of us: exploring daily violence, peacebuilding, and intercultural humility and resilience in interracial family communication - Mestrovich Seay, Aliah (Kansas State University, 2023)
The construction of interracial families in the United States was forbidden until legislation preventing antimiscegenation was revoked in 1967. As a result, interracial couples face many additional struggles not experienced by same-race partners, including marginalization as well as cross-cultural communication and socio-historical differences. It is challenging and sometimes impossible to have empathetic intersectional conversations about race and gender in the same breath within an interracial family in which family members hold both oppressor and Oppressed roles. As a result, communication about race and gender can feel dismissive to individuals who are facing oppression and disorienting to oppressors who have never been confronted or challenged by their racist or sexist blind spots. This dissertation seeks to push the boundaries of comfortable cross-cultural communication by exploring the ways we can embrace, accept, and learn to survive intersectional family communication from a point of critical hope, intercultural humility, and resilience, yet without negating conversations of race and gender and instead affirming the lived experiences of Oppressed people as we address our oppressor identities. As we engage in family communication, we find ways to address our role in daily violence, how we can be more adaptive and compassionate within these oppressor identities, and how to find peace within, between, and among people who are very different than ourselves. This dissertation addresses three questions: (1) How does gendered and racialized communication manifest in my own family experience? (2) How does my intercultural experience with daily violence manifest in my own family? (3) And finally, how do I implement peacebuilding and resilience strategies within myself and my interracial family? Those questions are also posed with the background of other interracial family experiences with intersectional healing. The results of the study indicate that RQ1 centered on (1) not escaping the white racial frame, (2) exploring the creative tension and transformative potential of talking about race and gender intentionally for the first time, (3) the unveiling of stock and concealed stories, (4) parenting biracial children through a lens of critical hope, and (5) storytelling as an act of peacebuilding and resilience. The three emergent themes for RQ2 were (1) personal experiences with daily violence on a spectrum, (2) the interconnectedness of childhood abuse, rape, and domestic violence in adulthood, and (3) violence as a ubiquitous phenomenon. Regarding RQ3, many tools for peacebuilding and resilience emerged during the study. Three conceptual frameworks were developed and explored with interracial families: intercultural listening from a critical whiteness and feminist perspective, the development of interracial family communication for intersectional healing and reconciliation (critical empathy, intercultural listening, and intercultural humility and resilience), as well as the development of intercultural humility and resilience (courageous conversations about race and gender, motivational interviewing techniques, and narrative therapy techniques). In addition to exploring these three conceptual frameworks, three additional peacebuilding and resilience tools were identified because of the research being conducted: the couples debrief, cross-culturally congruent listening, and hybrid culture. This study yielded several notable theoretical, methodological, and practice/engagement contributions to the field of leadership and communication. The theoretical contributions include listening as a recognized form of communication: Intercultural listening and cross-culturally congruent listening are frameworks that attribute more to listening than to speaking in critical intercultural communication. Intercultural listening attends to self and other awareness, power dynamics, and supporting the voices of marginalized peoples. Cross-culturally congruent listening creates opportunities to further peacebuilding in cross-cultural communication by creating feelings of connection and belonging as interracial families collectively engage in storytelling and narrative resilience. Additionally, successfully navigating critical intercultural communication takes place first within, between, and finally among people following a similar framework as peace within, peace between, and peace among (Galtung, 1969). Finally, fostering interracial family communication towards intersectional healing and reconciliation showcases the interracial family system as a catalyst to dismantle systemic oppression and daily violence that has the potential to impact larger educational and societal systems. Second, methodological contributions to the field include positioning art as emancipatory and community engaged. Arts-based narratives create a freedom of expression which are culturally responsive and support cross-cultural storytelling thus creating emerging freedom stories. Finally, practice/engagement contributions involve intentionality and commitment regarding communication about race and gender naturally leading to intersectional healing: interracial couples/families organically practiced the peacebuilding tools of critical empathy, intercultural listening, and intercultural humility. Additionally, community engagement and service contributed to intersectional healing and reconciliation and were defined by a desire to give back and provide support to the community and others struggling with daily violence, racialized and gender-based trauma, and cross-cultural communication. Lastly, utilizing the interracial family system as a catalyst for developing critical intercultural communication could be used to inform numerous fields including but not limited to education/teaching, therapy, civic and community development, and organizational leadership.
Keywords: Interracial family communication; Coinquiry; Critical evocative autoethnography; Critical intercultural communication; Racial reconciliation and healing; Intercultural listening